2020
DOI: 10.1101/2020.06.16.155747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nucleus accumbens melanin-concentrating hormone signaling promotes feeding in a sex-specific manner

Abstract: AbstractMelanin-concentrating hormone (MCH) is an orexigenic neuropeptide produced in the lateral hypothalamus and zona incerta that increases food intake. The neuronal pathways and behavioral mechanisms mediating the orexigenic effects of MCH are poorly understood, as is the extent to which MCH-mediated feeding outcomes are sex-dependent. Here we investigate the hypothesis that MCH-producing neurons act in the nucleus accumbens shell (ACBsh) to promote feeding behavior and mot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…To examine the role of CA1v to LS signaling on feeding behavior under free-feeding conditions, we examined meal pattern feeding analyses in the caspase vs. the control group (chronic CA1v-LS disconnection), and in the DREADDs group following CNO or vehicle (within-subjects design; reversible CA1v-LS disconnection). Results averaged over 5d revealed no significant effect of chronic shown that ICV CNO injections do not affect food intake in rats when tested under similar conditions (40). Collectively these findings show that reversible CA1v to LS disconnection increases food intake under free-feeding conditions, whereas food intake is not affected by chronic CA1v to LS ablation.…”
Section: Histological Analyses Confirmed Successful Viral Transfectiomentioning
confidence: 67%
See 2 more Smart Citations
“…To examine the role of CA1v to LS signaling on feeding behavior under free-feeding conditions, we examined meal pattern feeding analyses in the caspase vs. the control group (chronic CA1v-LS disconnection), and in the DREADDs group following CNO or vehicle (within-subjects design; reversible CA1v-LS disconnection). Results averaged over 5d revealed no significant effect of chronic shown that ICV CNO injections do not affect food intake in rats when tested under similar conditions (40). Collectively these findings show that reversible CA1v to LS disconnection increases food intake under free-feeding conditions, whereas food intake is not affected by chronic CA1v to LS ablation.…”
Section: Histological Analyses Confirmed Successful Viral Transfectiomentioning
confidence: 67%
“…3F&G). These results are unlikely based on nonselective effects of the CNO, as we've recently shown that ICV CNO injections do not affect food intake in rats when tested under similar conditions (37). Collectively these findings show that reversible CA1v to LS disconnection increases food intake under free-feeding conditions, whereas food intake is not affected by chronic CA1v to LS ablation.…”
Section: Histological Analyses Confirmed Successful Viral Transfection Of Ls-projecting Ca1vmentioning
confidence: 69%
See 1 more Smart Citation
“…The same population of ORX neurons projects to the ACBsh and PVT (Lee and Lee 2016). In terms of sex speci c behavioral networks, the ACB shell is where the lateral hypothalamic hunger peptide MCH neurons were shown to promote a male-speci c increase in consumption of chow and palatable foods (Terrill et al 2020).…”
Section: The Nucleus Accumbensmentioning
confidence: 99%
“…The role of coexpressed glutamate may support MCH‐mediated functions, including well‐established roles in the regulation of energy balance. Acute central MCH administration, 10 activation of MCH neurons, 11 or activation of the MCH receptor (MCHR1) stimulates feeding, 12‐14 and chronic MCH administration can promote body weight gain 15 . By contrast, mice that lack MCH or MCHR1 are lean, hyperactive and have increased energy expenditure 16‐18 .…”
Section: Introductionmentioning
confidence: 99%